Neuroform Atlas stent-assisted coiling of ruptured wide-necked anterior communicating artery aneurysms - Wang, Hongping; Hu, Shengli; Xu, Jianyi; Pei, Jian; Gao, Yunhe; Tian, Baogang; Wang, Dayong; Zheng, Yu; Xu, Xiang (Frontiers in Neurology, 2025)
One of the most crucial methods for treating wide-neck anterior communicating artery aneurysms is endovascular therapy. However, because of the small arterial diameter and volume with hematoma, endovascular embolization procedures for the treatment of burst wide-necked ACoA aneurysms are difficult. Few studies have been conducted to evaluate the Neuroform Atlas stent’s safety and effectiveness in treating wide-necked anterior communicating artery aneurysms, despite the fact that it has been frequently utilized to treat wide-necked aneurysms since its 2020 debut in China. Thus, this article’s goal is to examine the effectiveness and safety of Neuroform Atlas stent-assisted coiling in the management of anterior communicating artery burst wide-necked aneurysms. From August 2020 to June 2022, Neuroform Atlas stents were used to treat 30 patients with aneurysms of the ruptured wide-necked anterior connecting arteries. Neuroform Atlas stents were successfully and satisfactorily positioned in each of the 30 patients. Three patients had postoperative complications. Twenty-nine patients (96.7%) achieved an mRS score of ≤2, demonstrating satisfactory clinical outcomes, while one patient (3.3%) had an mRS score of 3, indicating poor prognosis. This pilot research shows that coiling ruptured wide-necked aneurysms of the anterior communicating artery with the use of a Neuroform Atlas stent is safe and effective.